PATHOMORFOLOGICAL STUDY OF ELECTRIC AND ULTRASONICALLY ACTIVATED TISSUE DISSECTION ON THE LOCAL ALTERATION EXPRESSION AND REPARATION PROCESS IN DIGESTIVE SYSTEM - TsivenkoА.І.; Sorokina, I.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
There have been shown the results in complex study of ultrasonically activated scalpel (UAS) and electric scalpel (ES) on digestive route. Specifics of after-operational period in experiment trial have been analyzed after performed interventions using UAS and ES. Basing on the results of obtained data there have been determined specifics of influence of different types of energy on the reparation processes. Obtained results showed advantages of ultrasonically activated scalpel in compare with electric scalpel.